THE EFFECT OF PERFORMANCE MEASUREMENT SYSTEM AND REMUNERATION TO EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CULTURE AS A MODERATING VARIABLE - Rokhimakhumullah, Dewi Noor Fatikhah (Journal of Innovation in Business and Economics, 2017)
This study aims to examine the effect of performance measurement system and remuneration on employee performance with organizational culture as moderating variable. This research uses survey research design with Partial Least Square (PLS) data analysis. Respondents in this study are 66 employees who have structural positions in KPP Madya Malang and KPP Pratama Batu. The results showed that the performance measurement system can improve employee performance. The results of this study demonstrated that organizational culture as a moderating variable was able to strengthen the relationship of performance measurement system and remuneration to employee performance. In addition, the results of the study was unable to prove that remuneration can improve the employees’ performance, because the remuneration given by the directorate general of taxes is not accompanied by a good performance appraisal.